Fatimid metalwork - Bilotto, Gregory (AUC Knowledge Fountain, 2012)
Metalwork in the Islamic world encompasses a large geographical area from Spain to India, over an enormous time-period with the earliest dynasty, the Rashidun Caliphate in 632 CE to the present. Islamic metalwork includes numerous categories of artisanship incorporating arms, armor, vessels, utensils, coins, jewelry, tools, scientific instruments, figurines and polycandela. The focus of this writing however will be to analyze the four categories of metal objects into which the vast bulk of Fatimid metalwork falls, namely vessels, utensils, figurines, lamps and polycandela.